The Effect Of Profitability, Political Connections, And Gender Diversity On Tax Avoidance - julvita, fadila muliana; Pusposari, Devy (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study aims to provide empirical evidence on the effects of profitability, board directors' political connections, and gender diversity on tax avoidance. The object of this study includes financial companies listed on the Indonesia Stock Exchange between 2022 and 2023, with a total sample of 22 companies. The secondary data used in this study are analyzed and processed using SPSS. Research results show that profitability and political connections positively affect tax avoidance, whereas gender diversity does not. This research supports agency and stakeholder theory and provides implications for companies' decision-making and the government's tax policies. It is suggested that further research use different measures for the political connection variable and select other sectors as research objects.